S-UTD-CH model in multiple diffractions - Tabakcıoğlu, Mehmet Barış (Taylor & Francis Ltd, 2016)
The propagation of electromagnetic waves in empty space is an extremely simplified case. Thus, the significant question is how an electromagnetic wave propagates in an environment with obstacles such as buildings, trees or hills. Electromagnetic waves are partially reflected and partially diffracted from these obstacles. To predict the relative path loss of electromagnetic waves at the receiving position, many electromagnetic-wave propagation models have been proposed. These propagation models can be classified into models based on numerical integration and those based on ray tracing. Uniform theory of diffraction (UTD) and slope-UTD (S-UTD) models are ray-tracing-based propagation models and are briefly explained in this paper. In addition, detailed information is provided about the improved slope UTD model, which is called the S-UTD with Convex Hull (S-UTD-CH) model. The fundamentals of the S-UTD-CH model are the S-UTD, convex hull and Fresnel zone concept. In particular, the S-UTD-CH model can be applied to multiple diffraction scenarios in the transition region. Moreover, the S-UTD-CH model is considered an optimum model in terms of its accuracy and calculation or computation time. Widespread simulation results are provided to compare the models based on theoretical rays in terms of prediction accuracy and computation time. To compare these models, different operation frequencies and transmitting antenna heights are considered by using a high-performance computing technique.
Keywords: numerical integration technique; radio wave propagation; high-performance computing; Electromagnetic wave diffraction; S-UTD-CH model; ray-theory-based models